Pengaruh Penggunaan Paper Mode Berbasis Aplikasi Quizizz terhadap Hasil Belajar Matematika Siswa SDIT Khairur Rahman - Nurhaidah Anggraeni Putri; Sapri Sapri; Lailatun Nur Kamalia Siregar (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
The objectives of this study were, 1) to determine the mathematics learning outcomes of SDIT Khairur Rahman students without using the Quizizz application-based paper mode, 2) the use of the Quizizz application-based paper mode, 3) the significant effect of using the Quizizz application-based paper mode on the learning outcomes of SDIT Khairur Rahman students. This research methodology uses quantitative research using the Quasi Experiment method (pseudo experiment) which is a development of the true experiment design. This research was conducted at SDIT Khairur Rahman, located on Jl. Arief Rahman Hakim Gg. Sukahati No. 1 Kel. Tegal Sari III, Kec. Medan Area, Medan City, North Sumatra. The population and sample of this study were all 3rd grade students consisting of 2 classes, namely the experimental class and the control class totaling 52 students. The test instruments used were pre-test and post-test in the form of multiple choice. The type of data analysis carried out by analyzing the Paired Sample T-Test test. The results of this study indicate 1) student learning outcomes without using the Quizizz application-based paper mode obtained an average pre-test score of 32.08 and post-test 63.96. 2) student learning outcomes using the Quizizz application-based paper mode obtained an average pre-test value of 48.00 and post-test 91.80. 3) there is an effect of using paper mode based on the Quizizz application on the learning outcomes of SDIT Khairur Rahman students. This is evidenced by the results of the Paired Sample T-Test test Sig value. 0.00 <0.05 so that Ha is accepted and Ho is rejected. Thus, the use of paper mode based on the Quizizz application can be applied by teachers to improve student learning outcomes.